Implementation of the laboratory quality management system (ISO 15189): Experience from Bugando Medical Centre Clinical Laboratory - Mwanza, Tanzania - Medard Beyanga; Lisa Gerwing-Adima; Kahima Jackson; Benjamin Majaliwa; Henrico Shimba; Simon Ezekiel; Charles Massambu; Dickson Majige; Michael Mwasegaka; Wilson Mtotela; Patrick Mateta; Christa Kasang (AOSIS, 2018)
Background: Use of laboratory evidence-based patient health care in Tanzania remains a complex problem, as with many other countries in sub-Saharan Africa. As at 2010, 39 African countries, including Tanzania, had no clinical laboratories that met the minimum requirements for international laboratory standards (International Organization for Standardization [ISO] 15189).   Objective: The aim of this article is to share experience from Bugando Medical Centre laboratory's milestones in reaching ISO 15189 accreditation.   Methods: Mentors to address the laboratory management and technical requirements performed a gap analysis using the Southern African Development Community Accreditation system checklist. Several non-conformances were detected. System and technical procedures were developed, approved and communicated. Quality indicators were established to measure laboratory improvement and to identify issues which require immediate and preventive actions.   Results: The departments' external quality assessment performance increased after ISO 15189 implementation (e.g. Parasitology from 45% to 100%, Molecular Biology from no records to 100%, Biochemistry 50% to 95%, Tuberculosis Microscopy 60% to 100%, and Microbiology from 48.1% to 100%). There was a reduction in complaints, from eight to two per week. Rejected samples were reduced from 7.2% to 1.2%. Turn-around time was not recorded before implementation but reached 92% (1644/1786) of the defined targets, and the proportion of contamination in blood cultures decreased from 16% to 4%.   Conclusion: Our experience suggests that the implementation of a quality management system is possible in resource-limited countries like Tanzania. Mentorship is necessary and should be done by professional laboratory mentors trained in quality management systems. Financial resources and motivated staff are key to achieving ISO 15189 accreditation.